Transformasi Nilai Moderasi Melalui Seni Lagu Qur'any: Warisan Spiritual KH. M. Qoyim Ya'qub dalam Membentuk Karakter Jamaah Pengajian Kamisan - Siti Zuliani (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
There are two aims of this research, namely to describe moderate values through Qur'any songs and to describe the process of forming moderate attitudes through the Qur'any by KH. M. Qoyim Ya'qub (late). The moderate values contained in the song Qur'any by KH. M. Qoyim Ya'qub namely: a. National Commitment, an example of song title: Choose a Leader with the sholawat song genre entitled Addiinulana. b. Tolerance. Examples of song titles: 1). Hai Kafir with the sholawat song genre entitled Thola'al Badru. 2). Forgive the Lay People with the sholawat song genre entitled An Nabi Sholuu Alaihi. 3). Avoid looking for people's faults with the sholawat song genre entitled Ya Rasulullah (version of the Indian song Tum Hi Ho). 4). The morals of the sholawat song genre are entitled Kun Anta. The process of forming a moderate attitude through the song Qur'any by KH. M. Qoyim Ya'qub (late) went through several stages: a. Stage 1: Understanding. At this stage, listeners of Qur'any songs first understand the text of the songs, especially the song titles which contain moderate values. b. Stage 2: Internalization. After understanding the content of the Qur'any song, listeners need to internalize it through playing the song repeatedly, discussion, and practice. c. Stage 3: Strengthening moderate values, through reading relevant books and participating in religious activities.